Hydrogen peroxide application improves quinoa performance by affecting physiological and biochemical mechanisms under water‐deficit conditions. (24th April 2018) - Iqbal, H.; Yaning, C.; Waqas, M.; Rehman, H.; Shareef, M.; Iqbal, S.
Abstract: Quinoa performance reduces under water‐limited conditions and can be improved through exogenous application of stress signalling molecule such as hydrogen peroxide (H2 O2 ). This study was conducted to elucidate the role of H2 O2 in quinoa at two water regimes maintained as full irrigated at 100% field capacity (FC~28% soil volumetric water contents; SVWC) and at 60% FC (~17% SVWC) as drought stress. Hydrogen peroxide concentrations, that is 80 mm for seed priming and 15 mm as foliar spray, were used from our preliminary experiments. Drought stress significantly reduced the plant growth, water status, photosynthetic activity and increased reactive oxygen species production (H2 O2 and O2 − ) resulting in higher oxidative damage in quinoa. Exogenous applied H2 O2 as priming agent improved emergence attributes by earlier emergence and made quinoa more tolerant to upcoming drought stress. Nevertheless, exogenously applied H2 O2 exhibited significantly higher stomatal conductance (34%), transpiration rate (39%), photosynthetic rate (42%), chlorophyll content index (36%), proline (19%) and total soluble sugar contents (14%) with respect to non‐treated plants under water‐deficit conditions. The H2 O2 application regulated the Abscisic acid (ABA) concentration under both conditions and reduced it by 30% in drought‐stressed plants as compared to non‐treated stressed plants. The exogenous application also enhanced the enzymatic antioxidants activities, including SOD, POD, CAT and APX by 32%, 31%, 34% and 53%, respectively, in quinoa plants under drought stress. We conclude that exogenous applied H2 O2 improved quinoa performance under drought stress is associated with higher accumulation of osmolytes, regulating ABA level and enhanced enzymatic antioxidant activities.